2012
DOI: 10.1097/sap.0b013e31823f3df0
|View full text |Cite
|
Sign up to set email alerts
|

To Everything There Is a Season

Abstract: Summer and winter were the peak seasons of resource utilization at our burn center, in terms of length and variability of ICU and hospital stays, as well as total hospital charges. Such seasonal change may be related to acuity of burn injury but not number of burn admissions. To improve operational efficiency and maximize patient throughput, resource allocation should be structured to anticipate seasonal changes, so that supply of services matches demand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Previous studies investigating temporal variations of burn inpatient admissions in the United States have had limited sample sizes representing a few states [ 5 , 11 , 19 ]; these studies’ conclusions have not been congruent and can only be applied to the state where each study was conducted. Our analysis represents pediatric burn patients nationally and shows a 31.8% increased likelihood for patients to be admitted during the month of July.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies investigating temporal variations of burn inpatient admissions in the United States have had limited sample sizes representing a few states [ 5 , 11 , 19 ]; these studies’ conclusions have not been congruent and can only be applied to the state where each study was conducted. Our analysis represents pediatric burn patients nationally and shows a 31.8% increased likelihood for patients to be admitted during the month of July.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis represents pediatric burn patients nationally and shows a 31.8% increased likelihood for patients to be admitted during the month of July. Some smaller studies have demonstrated higher rates of hospital admissions during winter months, correlating with increased scald injuries possibly caused by consumption of hot beverages and use of electric heaters [ 11 ]. Our data, however, does not suggest a national increase of burn injury admissions during winter months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prevention measures initiated in France over the period 2009–2014 reduced the incidence of burn injuries [1] . Although the seasonality and/or time of day of burn injuries has been extensively studied, a clear consensus on seasonal, monthly or daily patterns has not emerged [2] , [3] , [4] . In England and Wales, child burn injuries are most frequent between 4 pm and 7pm and are more frequent at the weekend than during the school/work week, i.e.…”
Section: Introductionmentioning
confidence: 99%